Efektivitas Prenatal Yoga Untuk Mencegah Rupture Perineum Di Bpm Dewi Chandra Ningrum Karanganyar - Siti Farida; Sri Wahyuningsih Nugraheni (Universitas Duta Bangsa Surakarta, 2021)
Perineal rupture often occurs during normal labor. Perineal rupture is a tear in the perineum that occurs as a result of the process of leaving the fetus from the uterus. Perineal rupture can harm both the mother and the fetus if not treated properly, and can cause complications, including bleeding, hematoma, fistula, and infection. Bleeding that comes out of the birth canal shortly after the newborn is born, the source and amount of bleeding must be ascertained so that it can be treated according to the cause. One of the causes of postpartum hemorrhage is due to perineal tears. There are several factors that can cause perinium tears, one of which is a stiff perineum. A stiff perineal condition can affect the second stage of labor so that it can increase the risk of death for the fetus and can cause extensive birth canal damage during labor. A stiff perineum can be anticipated from the time of pregnancy through various efforts, one of which is by doing prenatal yoga exercises. Prenatal yoga can provide benefits in training the perineal muscles to be stronger and stretchier during labor, so that making labor easier. The purpose of this study was to determine the effectiveness of prenatal yoga in preventing perineal rupture using a case control survey research design / design, retrospective approach. The sampling technique used was quota sampling. Based on the results of the Chi Square statistical test, it can be seen that p value = 0.017, where the p value is <α (0.05), so it can be concluded that prenatal yoga has a significant relationship with the incidence of perineal rupture in labor mothers.